Impact of Analgesia on the Course of Spontaneous Labor in Women with Diabetes Mellitus - M. I. Neimark; A. I. Kovalev (Общая реаниматология, 2013)
Objective: to improve the results of spontaneous labor in female patients with diabetes mellitus (DM). Subjects and methods. The results of physiological labor analgesia were analyzed in 140 patients. The parturients were divided into 3 groups: 1) 40 parturients in whom analgesia was performed by the intravenous administration of promedol; 2) 40 parturients in whom analgesia was done by the fractional administration of 0.2% ropivacaine hydrochloride into the epidural space; 3) 40 parturients in whom analgesia was carried out with intravenous paracetamol 2000—3000 mg. In all the patients, the investigators estimated central hemodynamic parameters by echocardiography, the efficiency of labor analgesia according to the scale described by N. N. Rasstrigina and B. V. Shnaider, as well as blood glucose levels, fetal status by a cardiotocographic technique, and neonatal status by Apgar scores at 1 and 5 minutes of life. Results. Analgesia quality assessment established that the best analgesic effect was achieved in the patients in Group 2 where 75.0% of the parturients had 8—10 scores. A comparative analysis of carbohydrate metabolic parameters also ascertained that the most steady-state and physiological glycemic level was recorded in Group 2 patients throughout the study. In addition, epidural analgesia versus other analgesic techniques provides the most steady-state hemodynamic parameters during labor, which promotes improved labor and has a beneficial effect on fetal and neonatal states. Conclusion. Glycemic levels during labor and delivery can be optimized in patients with DM only if adequate analgesia is achieved. By ensuring adequate labor analgesia, epidural analgesia normalizes glycemic and central hemodynamic parameters, favors elimination of delivery abnormalities, and has a beneficial effect on fetal and neonatal states. Key words: epidural analgesia, diabetes mellitus, spontaneous labor.